175 Surgical vs Nonoperative Management of Type II Odontoid Process Fractures in Octogenarians. (August 2015) - Graffeo, Christopher Salvatore; Perry, Avital; Puffer, Ross; Carlstrom, Lucas; Mallory, Grant William; Clarke, Michelle J.
Abstract : INTRODUCTION: Odontoid fracture is a common injury, particularly in elderly, fall-prone patients. Previous studies comparing surgical and nonoperative management have classified elderly patients as all individuals over 65 years, or those 65 to 80 years. We compare surgical and nonoperative management in octogenarians (>79 years), a medically distinct population. METHODS: A prospectively maintained trauma database was reviewed for all C2 fractures between 1998 and 2014. Blinded radiographic review confirmed Anderson/D'Alonzo type II fracture pattern. Outcomes included surgical intervention, cord injury, additional cervical fracture, Glasgow Coma Score (GCS), Abbreviated Injury Scale (AIS), Injury Severity Score (ISS), and 30-day and 1-year mortality. Statistical tests included student's t, χ 2, Fisher's exact, Kaplan-Meier, Cox proportional hazard. RESULTS: One hundred eleven patients with type II fractures were identified. Mortality or 1-year follow-up was available for 100%. Seventeen underwent surgery (20%). Mean age at injury was 87 (range 80-104, 55% female). Mean time to mortality or last follow-up was 22 months (range 0-129). Overall mortality was 26% at 30 days and 41% at 1 year. There was a trend toward longer median survival after surgery (69 vs 40 months, P = .66), although there was no mortality difference at 1 year (41% vs 41%, P = .98). Cord injury was associated with 30-day and 1-year mortality (OR 8.3 P = .0093; OR 9.6 P = .0122). Glasgow Coma Scale (GCS), American Spinal Injury Association Impairment Scale (AIS), and Injury Severity Score (ISS) were associated with 30-day mortality ( P < .0001; P = .0015; P = .0029); GCS and AIS were significantly associated with 1-year mortality ( P = .0027; P = .0113). Halo placement and additional cervical fracture were not associated with increased mortality. Surgery was not associated with any outcomes. Kaplan-Meier analysis did not show an association between any variable and survival. CONCLUSION: Type II odontoid fracture is highly morbid among octogenarians, with 1-year mortality approaching 1-in-2. Neither surgical nor nonoperative management is associated with a survival benefit. Cord injury, GCS, AIS, and ISS are significant predictors of poor prognosis.